2004
DOI: 10.1289/ehp.6477
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl sulfate inhibits NO production via threonine phosphorylation of eNOS.

Abstract: Exposure to excessive vanadium occurs in some occupations and with consumption of some dietary regimens for weight reduction and body building. Because vanadium is vasoactive, individuals exposed to excessive vanadium may develop adverse vascular effects. We have previously shown that vanadyl sulfate causes acute pulmonary vasoconstriction, which could be attributed in part to inhibition of nitric oxide production. In the present study we investigated whether NO inhibition was related to phosphorylation of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
2
15
0
1
Order By: Relevance
“…Our evidence that (R)-methanandamide produced an Akt-mediated phosphorylation at Ser 1177 is in agreement with the results reported by Sessa and colleagues in bovine aortic endothelial cells stimulated with sphingosine-1-phosphate (Igarashi and Michel, 2001;Lin et al, 2003). Protein kinase C signaling acts in opposition by phosphorylating Thr 495 residues and promoting phosphatase-mediated Ser 1177 dephosphorylation (Li et al, 2004). Our data are consistent with eNOS activation via a PI3-kinase-Akt pathway that involves a mechanism requiring G i activation.…”
Section: Discussionsupporting
confidence: 93%
“…Our evidence that (R)-methanandamide produced an Akt-mediated phosphorylation at Ser 1177 is in agreement with the results reported by Sessa and colleagues in bovine aortic endothelial cells stimulated with sphingosine-1-phosphate (Igarashi and Michel, 2001;Lin et al, 2003). Protein kinase C signaling acts in opposition by phosphorylating Thr 495 residues and promoting phosphatase-mediated Ser 1177 dephosphorylation (Li et al, 2004). Our data are consistent with eNOS activation via a PI3-kinase-Akt pathway that involves a mechanism requiring G i activation.…”
Section: Discussionsupporting
confidence: 93%
“…H 2 O 2 produced by NAD(P)H oxidase contributed to PMinduced vasoconstriction because DPI inhibited UP-induced constriction of PA ring and intravascular administration of extracellular H 2 O 2 produced by glucose and glucose oxidase produced acute vasoconstriction in perfused lungs. We and others have previously identified several signaling pathways that mediate PM-induced vasoconstriction, including epidermal growth factor receptor, angiotensin II receptor subtype 1, endothelins, and NO (8,25,27,31,32,44). Our results indicate that H 2 O 2 produced by the membrane NAD(P)H oxidase should also be added to the list.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we have recently shown that Hsp90 inhibition with radicicol, that reduced Hsp90 interaction with their client proteins, produced a significant reduction in renal plasma flow and glomerular filtration rate, an effect that was associated with a decreased urinary excretion of nitrites and nitrates (NO 2 /NO 3 ), suggesting that the disruption of eNOS-Hsp90 complex reduced renal NO synthesis [20]. In addition, previous studies have shown that the disruption of eNOS/Hsp90 complex promotes not only the reduction anion by eNOS [8,9,21,22]. Even though there is enough evidence about the Hsp90/eNOS coupling and uncoupling in NO and O 2 -generation, respectively, the specific role of Hsp90α and Hsp90β in this pathway have not been completely addressed.…”
Section: Discussionmentioning
confidence: 98%